Liraglutide Regulates the Kidney and Liver in Diabetic Nephropathy Rats through the miR-34a/SIRT1 Pathway - Shan Xiao; Ye Yang; Yue-Tong Liu; Jun Zhu (Journal of Diabetes Research, 2021)
Purpose. To explore the regulatory effects of liraglutide on the kidney and liver through the miR-34a/SIRT1 pathway with related factors in diabetic nephropathy (DN) rats. Methods. DN rats were randomly divided into two groups (n=10) and were injected with liraglutide or normal saline twice a day. The 24-hour urine microalbumin content and biochemical index levels were measured. qRT-PCR was performed to detect the expression of miR-34a in the kidney and liver tissues. The levels of SIRT1, HIF-1a, Egr-1, and TGF-β1 in kidney and liver tissues were determined using qRT-PCR, western blot, and immunohistochemistry. Electron microscopy and HE staining were used to observe the ultrastructure and pathological changes. Results. Liraglutide treatment in DN rats decreased blood glucose, 24-hour urine microalbumin, TC, TG, LDL-C, UA, Cr, UREA, ALT, and AST levels and increased the level of HDL-C (P<0.05). Compared with the control group, the miR-34a levels were significantly decreased in kidney and liver tissues followed by liraglutide treatment (P<0.05). The levels of SIRT1 in the liraglutide group are significantly higher than those in the control group with the kidney and liver tissues (P<0.05). Conversely, the contents of HIF-1a, Egr-1, and TGF-β1 were significantly lower in the liraglutide group than in the control group (P<0.05). Electron microscopy showed that the kidney of the liraglutide-treated group exhibited minor broadening of the mesangial areas, fewer deposits, and a well-organized foot process. HE staining revealed that the kidney of the liraglutide-treated rats had a more regular morphology of the glomerulus and Bowman sac cavity and lighter tubular edema. Additionally, the liraglutide-treated DN rats had a clear hepatic structure, a lower degree of steatosis, and mild inflammatory cell infiltration. Conclusion. Liraglutide, through its effect on the miR-34a/SIRT1 pathway, may have a protective role in the kidney and liver of DN rats.